NOVEL PEROXIREDOXIN DEFENSE SYSTEM FROM MYCOBACTERIUM TUBERCULOSIS - LIMA CHRISTOPHER D; BRYK RUSLANA; NATHAN CARL F (2007)
The present invention relates to methods of preventing and treating tuberculosis in a subject infected with Mycobacterium tuberculosis. The method involves inhibiting AhpD in the subject under conditions effective to make the pathogen susceptible to antimicrobial reactive nitrogen intermediates or reactive oxygen intermediates. The present invention also relates to methods of preventing and treating tuberculosis in a subject infected with Mycobacterium tuberculosis involving inhibiting dihydrolipoamide dehydrogenase or dihydrolipoamide succinyltransferase in Mycobacterium tuberculosis in the subject under conditions effective to make the pathogen susceptible to antimicrobial reactive nitrogen intermediates or reactive oxygen intermediates. Also disclosed are methods for identifying candidate compounds suitable for treatment or prevention of tuberculosis. Methods of producing an AhpD crystal suitable for X-ray diffraction as well as methods for designing a compound suitable for treatment or prevention of tuberculosis and compounds suitable for treatment or prevention of tuberculosis are also disclosed.